2013
DOI: 10.1038/nature11769
|View full text |Cite
|
Sign up to set email alerts
|

Flows of gas through a protoplanetary gap

Abstract: Instrumental setup and data reduction ALMA setup. ALMA Band 7 observations of HD142527 were carried out in the night of June 2 2012. The precipitable water vapor in the atmosphere was stable between 1.4 and 1.8 mm, with clear sky conditions. The ALMA correlator was configured in the Frequency Division Mode (FDM) to provide 468.750 MHz bandwidth in four different spectral windows at 122.07 kHz resolution (0.1 km/s) per channel. Each spectral window was positioned in order to target the CO(3-2) transition at 345… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
412
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 361 publications
(451 citation statements)
references
References 40 publications
29
412
5
Order By: Relevance
“…As our models assume p=3.5, an increase in the maximum dust grain size by a factor of ∼75, say, from 1 mm to 10 cm, could explain this drop in flux. This is borne out by a number of studies that have found cavities, gaps, spiral arms, and other asymmetries in Class II disks that may indicate the presence of planets (Isella et al 2010Andrews et al 2011Andrews et al , 2016Casassus et al 2013; Weidenschilling 1977). We find that our Class I disks, on average, are more massive than the Taurus Class II disks, likely due to dust grain processing hiding matter in larger bodies in the older Class II disks.…”
Section: Class I Versus Class Ii Disk Massesmentioning
confidence: 52%
“…As our models assume p=3.5, an increase in the maximum dust grain size by a factor of ∼75, say, from 1 mm to 10 cm, could explain this drop in flux. This is borne out by a number of studies that have found cavities, gaps, spiral arms, and other asymmetries in Class II disks that may indicate the presence of planets (Isella et al 2010Andrews et al 2011Andrews et al , 2016Casassus et al 2013; Weidenschilling 1977). We find that our Class I disks, on average, are more massive than the Taurus Class II disks, likely due to dust grain processing hiding matter in larger bodies in the older Class II disks.…”
Section: Class I Versus Class Ii Disk Massesmentioning
confidence: 52%
“…We also followed a second method, based on non-parametric Bayesian image synthesis. We fit an image model to the observations at each spectral window, and in the visibility domain, by minimizing the weighted least-square distance, as previously performed in other multi-frequency analyses of ALMA data [20,32] . Since both approaches provided very similar trends, we adopted the Bayesian image synthesis, as it potentially allows for slightly finer angular detail, and the residual were more homogeneous (i.e.…”
Section: V883mentioning
confidence: 99%
“…As the inner discs are depleted by accretion onto the stars on timescales of few 10 3 yr, replenishing material must be transferred from the outer reservoir in order to fuel 1 planet formation (which occurs on timescales of ∼1 Myr). Gas flowing through disc cavities has been detected in single star systems 6 . A circumbinary disc was discovered around the young low-mass binary system GGTau-A 7 , which has recently been proven to be a hierarchical triple system 8 .…”
mentioning
confidence: 99%